Predicting the effect of individual weight-bearing on tibial load and fracture healing after tibial plateau fractures–introduction of a biomechanical simulation model - Andres, Annchristin; Roland, Michael; Wickert, Kerstin; Diebels, Stefan; Truhn, Daniel; Histing, Tina; Braun, Benedikt (Frontiers in Bioengineering and Biotechnology, 2025)
PurposeThe prescribed amount of weight-bearing after tibial plateau fractures is controversial because it affects osteosynthetic construct stability and fracture healing. We aim to introduce a simulation model that adequately predicts the effects of different weight-bearing amounts on stability and healing, based on the patient’s individual fracture pattern and treatment construct.MethodsTo safely test different amounts of weight-bearing limits, we first extracted knee joint forces for different weight-bearing limits from musculoskeletal simulation based on monitoring data of 22 uninjured participants. Correct loading was ensured with a force-measuring insole. We then tested three patients after tibial plateau fracture with their current weight-bearing level and constructed a simulation model determining implant stress, knee joint force, and fracture gap interfragmentary strain. The patient-specific weight-bearing level was then substituted for weight-normalized uninjured participant data to test different weight-bearing levels in the simulation model.ResultsThe simulation model calculated individual construct stiffness and interfragmentary strain at different weight-bearing levels following the clinical course. When comparing the patient’s individual weight-bearing input with the weight-normalized input of the uninjured participants at the same level, comparable knee joint forces were extracted, showing the feasibility of this approach.ConclusionUsing an adapted reference movement database, the model allows the determination of safe weight-bearing ranges concerning construct stability and fracture healing based on individual fracture morphology and treatment without exposing patients to excessive weight-bearing. Future studies can test this approach in more extensive patient-number studies and different treatment situations.